PROSPEK USAHATANI KAKAO KECAMATAN BANDAR BARU KABUPATEN PIDIE JAYA - Nova Sriwanda (Universitas Teuku Umar, 2018)
This study aims to determine the business prospects of cocoa plantations, determine the level of sensitivity of the amount of production and strategic development of cocoa farming, in supporting the expansion of cocoa farming area in the district of Pidie Jaya Bandar Baru. The data used are primary data obtained from direct interviews with cocoa farmers, secondary data were obtained from literature study and data retrieval from related agencies such as the BPS Pidie Jaya wich related to this research. The analysis is the analysis begins with the analysis of financial and SWOT analysis. The results showed a financial analysis technique based on a cocoa farm to be developed with NPV> 0, Net B / C> 0 and IRR> of the interest rate applicable. For sensitivity analysis on cocoa farming and production decline in the price of cocoa to cocoa farming so this condition is not feasible to develop. The position of the development strategy of farming cocoa in the position of an aggressive strategy is to establish areas that have the potential for the development of farming cocoa in District Bandar Baru and required government intervention more intensively in problem solving eradication of pests and diseases that attack cocoa. Thisstrategy can be used if the cocoa farmer has the opportunity and strength so that it can take advantage of opportunities with the powers that be, because both have positive difference calculated value is equal to 0.41 and 1.5.